Narratives of internal migration experiences, health/well-being issues among females working as head-porters (Kayayei) in Ghana - Kuyini, Ahmed Bawa (2020)
Purpose– This study aims to explore the internal migration experiences and health/well-being issues of 38girls andwomenworkingasKayayei(head-porters)inAccra,Ghana. Design/methodology/approach– Datawerecollectedfromseven focusgroupinterviewsessions,and thematicanalysis wasusedtoanalysethedata. Findings– The results revealed the geographic, structural and family issues that promote increased migration of females to the cities. The findings betray the potential negative effects of migration on the participants’ quality of life, including accessing health services. They also suggest that the Kayayei phenomenon is a significant child protection, health/well-being concern yet to be given adequate attention in ways that consider the implications of such large internal migration of females on the overall humanresourcedevelopmentcapacitiesofruralcommunities. Originality/value– This isanoriginalstudywithdatacollectedtoexploreinternalruraltourbanmigration anditseffect onhealthandwell-beingofyounggirlsandwomen. Keywords Ghana,Healthandwell-being, Femalemigrant workers,Migrationexperiences PapertypeResearchpaper